Pelatihan Budidaya Maggot BSF Di Kampung Unggas Desa Teruwai Kecamatan Pujut Lombok Tengah - Dwi K. Purnamasari; Sumiati Sumiati; Syamsuhaidi Syamsuhaidi; K.G. Wiryawan; Erwan Erwan; Vebera M. Maslami (Universitas Mataram, 2023)
The service activity aims to train the Teruwai Village Poultry community in cultivating BSF maggots to overcome the problem of livestock waste and kitchen organic waste. Activities were carried out in two activity stages, namely: Stage 1, socialization on BSF maggot cultivation, and Stage II, training on BSF maggot cultivation using poultry farm waste and kitchen organic waste. The targets are village administrators, communities, and poultry farmer groups. The training begins with the hatching stage, rearing mini larvae to become adult maggots, followed by the process of harvesting adult maggots and prepupae and flies, to harvesting eggs as well as harvesting used maggot media (kasgot) which has the potential to be used as fertilizer. The service activities were enthusiastically welcomed by the village head and his staff, breeders, and the Teruwai Village community. The attendance of service participants reached approximately 40 people. There has been an increase in public knowledge about the potential of maggots as poultry feed. The Village Government is committed to trying to cultivate maggots as a pilot project for the community by training each household to sort organic waste and collect it in one location to be used as a medium for growing BSF maggots. The Village Government hopes that this activity will not only solve environmental problems but also overcome the problem of the high price of poultry feed, and will increase people’s income with economically valuable maggot and cashew products.